Outline for Managing Irrigation of Florida Citrus with High Salinity Water - Brian J. Boman; Eddie W. Stover (EDIS)
This is Document No. ABE 332, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2002.